Propagación vegetativa de badea (Pasiflora quadragularis L) por medio de ramillas utilizando hormonas Ana y Aib en el cantón Buena Fé - Angulo Moreno, Oswaldo Daniel (2015)
The work was to evaluate the vegetative propagation through twig badea (Passiflora quadragularis L) using hormones NAA and IBA ,, including indole-butyric acid (IBA) and naphthaleneacetic acid (NAA), in doses of 750 mg kg- 1 of AIB + 750 mg kg -1 SD ANA, 1000 mg kg-1 of AIB +1000 mg kg -1 SD ANA, 1200 mg kg-1 of AIB + 1200 mg kg -1 SD ANA and a control (without hormones) with substrate dirt, sand and dust burn rice. Design applied completely randomized with four treatments and five replications and eight observations per experimental unit. At 45 days the percentage of seizure, rooting percentage, root number, root length increased by applying the Tukey test to determine significant differences between the mean of the treatments was evaluated. An analysis of the results and interpretation of experimental evidence is concluded that the treatment achieved the highest number and average root length was the T4 (1200 mg kg -1 ANA + 1200 mg kg-1 IBA) with 4.98 numbers roots and 7.68 cm respectively. The average percentage of seizure was between 67.18 and 69.0%. The average highest rooting percentage was the T4 treatment (1200 mg kg -1 ANA + 1200 mg kg-1 IBA) with 66.18%. The treatment had the best performance was the T1 (control) with 70.57% of cost effectiveness.